Electrochemistry : A Guide for Newcomers - Baumgärtel, Helmut (De Gruyter, 2019)
Electrochemical processes are long known but are becoming increasingly important again, due to modern applications, such as electro-mobility or energy storage. Thus, electrochemistry is not only a topic for chemists and physicists, but also for technical engineers. This book addresses all aspects of electrochemistry, which are important in these days: electrodes, corrosion, interphases, processes, energy storage, analytical methods, and sensors.